1999
DOI: 10.2307/176923
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial-Aquatic Linkages: Riparian Arthropod Inputs Alter Trophic Cascades in a Stream Food Web

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Dynamics of headwater stream ecosystems are generally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Thus, terrestrial insects may constitute an important energy subsidy for YOY S. alpinus during late summer, a period when interspecific interactions from S. salar and C. poecilopus may be high (Gabler & Amundsen, 1999, 2010. The role of terrestrial insects in stream food webs is indisputable (Nakano et al, 1999b), but the extensive contribution of terrestrial prey in the diet of small-sized S. alpinus observed in this study is very high. The consumption of this resource can have a direct consequence on fish growth (Sweka & Hartman, 2008) and facilitate niche partitioning between sympatric fish species through fish segregation in water column use (Nakano et al, 1999a;Sánchez-Hernández et al, 2013).…”
mentioning
confidence: 61%
“…Thus, terrestrial insects may constitute an important energy subsidy for YOY S. alpinus during late summer, a period when interspecific interactions from S. salar and C. poecilopus may be high (Gabler & Amundsen, 1999, 2010. The role of terrestrial insects in stream food webs is indisputable (Nakano et al, 1999b), but the extensive contribution of terrestrial prey in the diet of small-sized S. alpinus observed in this study is very high. The consumption of this resource can have a direct consequence on fish growth (Sweka & Hartman, 2008) and facilitate niche partitioning between sympatric fish species through fish segregation in water column use (Nakano et al, 1999a;Sánchez-Hernández et al, 2013).…”
mentioning
confidence: 61%
“…Another kind of behavioral adjustment involves switching search methods (Stephens & Krebs 1986). Short-term switches or the short-term changes in food searching methods were observed and analysed in numerous animal groups as a rapid and reversible adaptation response to different conditions of food availability (Thomas 1974, Davies 1977, Recher et al 1983, Formanowicz & Bradley 1987, Grant & Noakes 1987, Village 1990, Bell 1991, Nakano et al 1999. The Ferruginous Duck is an excellent diver, but we have also highlighted other feeding methods less frequent than diving, but have crucial importance in the subventions of nutritional needs.…”
Section: Discussionmentioning
confidence: 95%
“…As several authors have demonstrated, subsidies (or their exclusion) can lead to trophic cascades and other community-level impacts (e.g., Nakano et al 1999;Sato et al 2016). There are certainly many examples of subsidies boosting production at lower trophic levels that contribute to bottom-up increases at higher trophic levels (e.g., Wallace et al 1999;Wipfli et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Additions or removal of sea wrack on small Caribbean islands has shown that this too is a key resource affecting recipient populations (e.g., Piovia-Scott et al 2011). Exclusion of terrestrial arthropods from dropping into a stream resulted in reduced growth and shifts in foraging by trout (Nakano et al 1999), and exclusion of nematomorph-infected crickets from streamsides resulted in much lower growth rates of char compared with control reaches (Sato et al 2011). Exclusion of adult aquatic insects from riparian areas show that many web-building spiders use this resource (Marczak and Richardson 2007).…”
Section: Quantitative Effects Of Experimental Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation